Business plan for a hospitality digital content distribution service - Jíra, Pavel; Pernica, Karel; Tyll, Ladislav; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2020)
The aim of this thesis is to explore a business plan for a video streaming service aimed at hospitality customers. The theoretical part reviews available literature on writing business plans and selects methods applicable for use in this business case. The practical part of the thesis sets the vision for the startup in the contemporary market context and explores the external environment of the proposed startup, estimating its perspective competitive position, necessary capabilities, and key concerns for achieving profitability.
Vedoucí práce: Karel Pernica
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: business administration/corporate finance and management [obor bakal. práce]; bakalářské práce; bachelor's theses